Feasibility of Composite Edible Coating Derived from Chitosan and Carboxymethyl Cellulose on Star Apple Quality during Post-harvest Preservation - N. P. Minh (Journal of Global Pharma Technology, 2019)
Star apple (Chrysophyllum cainito) is well known as non climacteric fruit with high antioxidant capacity, high nutritional and health benefit. Its pulp is very sweet with glucose as the main sugar. This fruit has a short shelf life due to its perishable nature. Edible coatings have been extensively applied in the fruit preservation as an alternative method to preserve foodstuffs, improve shelf life and control loss of firmness and moisture in fresh fruits. Hence, purpose of this research penetrated on the efficiency of composited edible coating film prepared from chitosan and carboxymetyl cellulose (CMC) in different formulas to preserve star apple fruit. Weight loss (%), firmness (N), total soluble solid (oBrix), and vitamin C were the key indicators used to monitor during 15 days of preservation. After chitosan-CMC coating, the weight loss rate was restrained, and higher firmness, total soluble solid, and vitamin C were reserved. Our finding revealed that chitosan 2.0% combined with CMC 1.0% was appropriate for extending self-life of this valuable fruit. There has been a great demand of emerging fruit packaging from chitosan-CMC composited coating as antibacterial and barrier film. Composited chitosan-CMC coating would have wide prospect in the preservation of other post-harvest fruits and vegetables.Keywords: Chrysophyllum cainito, Chitosan, CMC, Coating, Weight loss, Firmness, Soluble solid, Vitamin C.